Pharmacological targeting of the NMDAR/TRPM4 death signaling complex with a TwinF interface inhibitor prevents excitotoxicity-associated dendritic blebbing and organelle damage - Ramirez, Omar; Hellwig, Andrea; Zhang, Zihong; Bading, Hilmar (Cells, 2025)
Focal swellings of dendrites (“dendritic blebbing”) together with structural damage of mitochondria and the endoplasmic reticulum (ER) are morphological hallmarks of glutamate neurotoxicity, also known as excitotoxicity. These pathological alterations are generally thought to be caused by the so-called “overactivation” of N-methyl-D-aspartate receptors (NMDARs). Here, we demonstrate that the activation of extrasynaptic NMDARs, specifically when forming a protein-protein complex with TRPM4, drives these pathological traits. In contrast, strong activation of synaptic NMDARs fails to induce cell damage despite evoking plateau-type calcium signals that are comparable to those generated by activation of the NMDAR/TRPM4 complex, indicating that high intracellular calcium levels per se are not toxic to neurons. Using confocal laser scanning microscopy and transmission electron microscopy, we show that disrupting the NMDAR/TRPM4 complex using the recently discovered small-molecule TwinF interface inhibitor FP802 inhibits the NMDA-induced neurotoxicity-associated dendritic blebbing and structural damage to mitochondria and the ER. It also prevents, at least in part, the disruption of ER-mitochondria contact sites. These findings establish the NMDAR/TRPM4 complex as the trigger for the structural damage of dendrites and intracellular organelles associated with excitotoxicity. They also suggest that activation of the NMDAR/TRPM4 complex, in addition to inducing high-amplitude, plateau-type calcium signals, generates a second signal required for glutamate neurotoxicity (“two-hit hypothesis”). As structural damage to organelles, particularly mitochondria, is a common feature of many human neurodegenerative diseases, including Alzheimer’s disease and amyotrophic lateral sclerosis (ALS), TwinF interface inhibitors have the potential to provide neuroprotection across a broad spectrum of these diseases.